Outcome based education attributes for OSH programme based on industrial needs - Sukadarin, Ezrin Hani
Outcome based education approach is crucial part to be emphasized during Occupational Safety and Health curriculum development and implementation. It is undeniable that employability skills or soft skills reflects graduate employability and significance of the existence and sustainable of a program at the university. Therefor this study aimed to highlight the importance of a structured curriculum development starting from the development of Program Educational Objectives (PEO), the development of PO (Programme Outcome, and after that, the development of Course Outcome (CO). Continual Quality Improvement (CQI) for Occupational Safety and Health Program which is workshop with industrial advisory panel (IAP) and external examiner (EA) were also reported. Both activities are conducted to seek input for any improvement that can be done, so that the programme are sustain and marketable. Data of graduate employability shown that, the graduate of the OSH programme are marketable. Due to that, it is suggesting that the runner of the programme need to maintain the efforts to ensure the OSH program can be sustained and keep improved for time to time to meet the career market demands.